PTK6 mediated immune signatures revealed by single cell transcriptomic and multi omics big data analysis in cervical cancer - Fen Zhao; Huanxin Zhong; Lifang You; Yi Du; Changchang Huang (Discover Oncology)
Abstract Background Cervical cancer exhibits heterogeneous clinical outcomes, requiring improved prognostic tools. Single-cell RNA sequencing enables high-resolution analysis of tumor microenvironment cellular heterogeneity. This study developed a prognostic model for cervical cancer through single-cell transcriptomic analysis and immune infiltration characterization, focusing on PTK6 as a key biomarker. Methods We analyzed TCGA and GEO transcriptomic data with single-cell RNA sequencing datasets. Fifteen machine learning algorithms constructed prognostic models using immune infiltration-related genes. Single-cell analysis employed Seurat for cell clustering and annotation. PTK6 expression was validated in H8 and HeLa cell lines via RT-qPCR and siRNA knockdown experiments. Results Single-cell sequencing revealed distinct cellular populations including CD8T cells, CD4Tconv cells, and fibroblasts. The prognostic model achieved excellent performance with AUC values of 0.737–0.757 across 1–5 years. PTK6 showed significantly elevated expression in tumors and strong correlations with immune infiltration. Single-cell analysis confirmed PTK6 expression across multiple cell types. Functional validation demonstrated that PTK6 knockdown reduced HeLa cell proliferation, confirming its oncogenic role. Conclusion PTK6 emerges as a critical immune infiltration-related prognostic biomarker through single-cell transcriptomic analysis.